First Approaches to Integrate a Strain Gauge-Based Mass Detection System into a Miniaturized DSC-device. (2015) - Brandenburg, A.; Wappler, E.; Kita, J.; Moos, R.
Abstract: The integration of a mass detection system in an existing miniaturized differential scanning calorimeter device (DSC-MD) is shown in this study. With a size of only 11 mm x 40 mm x 1.3 mm, the DSC-MD exhibits a thermal resolution, which is comparable to conventional apparatuses. To allow for the determination of mass specific thermal properties, the integration of a mass sensing system based on screen-printed strain gauges onto the device was the focus of this work. By FEM-analysis, the device was simulated, the ideal positions of the strain gauges were identified, and the sensitivity of the mass sensing system was estimated. First tests show promising results in the range of 8 – 200 mg.